Implementasi Budaya Sekolah dalam Membangun Kesadaran Multikultural - Hasan, Munawir; Hermansyah , Hermansyah; Sukino, Arief (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
This study examines school culture's in creating an inclusive environment that supports diversity. This study uses a qualitative approach with a case study type at SD Negeri 03 Pontianak City. Data collection techniques include observation and interviews with the principal and Islamic Religious Education (PAI) teachers. The results of the study indicate that school culture contributes to creating an inclusive environment through three main aspects: (1) School cultural artefacts, such as the use of traditional clothing in school activities, classroom decorations that reflect cultural diversity, and equal religious learning facilities; (2) Values ​​and beliefs that are manifested through inclusive school rules, the formation of the Violence Prevention and Handling Team (TPPK), and the integration of regional languages ​​in learning to strengthen students' cultural identity; and (3) Basic assumptions reflected in cultural activities such as the robo-robo tradition and the celebration of the culmination of the sun, as well as the integration of multicultural values ​​in the curriculum. Implementing this school culture has built multicultural awareness in an inclusive environment, becoming a model for other schools in instilling tolerance and solidarity among students.